Korelasi Antara Tingkat Kebugaran Jasmani (Vo₂Max) Dan Indeks Massa Tubuh Mahasiswa Studi Ilmu Keolahragaan - Subarjah, Muhammad Akmal; Hasan, Rahman Muhammad; Prasetyo, Bayu Tri; Setiawan, Muhammad Arief; Rahayu, Selvia (Pusat Kajian Pendidikan Olahraga, Kesehatan, dan Rekreasi Jurusan Pendidikan Olahraga Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2025)
Physical fitness and body composition are important indicators in determining a person's physical condition, especially Sports Science students who are required to have optimal performance. This study aims to determine the relationship between physical fitness level as measured through VO₂Max and Body Mass Index (BMI) of students of the Sports Science Study Program, University of Singaperbangsa Karawang. The research method uses a correlational quantitative approach with a sample of 60 active students of the 2021–2023 class selected through purposive sampling. VO₂Max data is collected through the 12-minute Cooper Test, while BMI is calculated based on the formula of body weight (kg) divided by height squared (m²). The results showed a significant negative relationship between VO₂Max and BMI (r = –0.613; p < 0.05), which means that the higher the BMI, the lower the level of physical fitness. These findings reinforce the theory that body composition has an effect on a person's aerobic capacity. In conclusion, college students with a normal BMI tend to have a better VO₂Max than those who are overweight. This study recommends that students maintain an active lifestyle and balanced nutrition to support optimal physical fitness.